Serious health events and their impact on changes in subjective health and life satisfaction: The role of age and a positive view on ageing - Wurm, Susanne; Tomasik, Martin; Tesch-Römer, Clemens (European Journal of Ageing, 2008)
Various studies have pointed to the great importance of subjective health as an indicator for mortality in older age, while less is known about factors that contribute to changes of subjective (self-rated) health over time. Based on a nationwide longitudinal survey (German Ageing Survey, N = 1,286; initial age 40-85), two major findings emerged: first, the incidence of a serious health event caused greater changes in subjective health and life satisfaction in middle compared to older age. This was as expected because serious health events are less common in middle age and are correspondingly experienced more often as an "off-time event". Secondly, the study extended previous findings on the impact of a positive view of ageing on health by showing that this optimistic view positively affects subjective health and life satisfaction even in the face of a serious health event. Overall, the study indicates that a positive view on ageing is an important psychological resource in the case of a serious health event, both when it occurs on-time or off-time from a developmental perspective. © Springer-Verlag 2008.
Keywords: Life satisfaction; Longitudinal study; Positive view on ageing; Serious health event; Subjective (self-rated) health